Registros adicionales de aves para Hidalgo, México - Valencia-Herverth, J.; Valencia-Herverth, R.; Mendoza-Quijano, F. (Instituto de Ecología, A.C., 2008)
We report here 11 new records of birds from several localities on the northeast of the state of Hidalgo. In addition, the extension of the area of distribution of Tigrisoma mexicanum is indicated. Sampling sites have patches of evergreen seasonal forest, cloud forest, riparian and disturbed habitats. Of the recorded species, Vireo atricapilla is considered as Endangered by the NOM-059-ECOL-2001.